Middle Ear Administration of a Particulate Chitosan Gel in an in vivo Model of Cisplatin Ototoxicity - Videhult Pierre, Pernilla; Fransson, Anette; Kisiel, Marta Alina; Damberg, Peter; Nikkhou Aski, Sahar; Andersson, Mats; Hällgren, Lotta; Laurell, Göran (Frontiers in Cellular Neuroscience, 2019)
Background Middle ear (intratympanic; IT) administration is a promising therapeutic method as it offers the possibility of achieving high inner ear drug concentrations while maintaining low levels in the systemic compartment, thus minimizing the risk of systemic side-effects and drug-drug interactions. The issue of premature elimination through the Eustachian tube may be reduced by stabilizing drug solutions with a hydrogel. However, this raises the secondary issue of conductive hearing loss. Aim This study aimed to investigate the properties of a chitosan-based particulate hydrogel formulation when used as a drug carrier for IT administration in an in vivo model of ototoxicity. Material and methods Two particulate chitosan-based IT delivery systems, Thio-25 and Thio-40, were investigated in albino guinea pigs (n=94). Both contained the hearing protecting drug candidate sodium thiosulfate but differed in terms of the concentration of chitosan gel particles (25% versus 40%). The safety of the two systems was explored in vivo. The most promising system was thereafter investigated in guinea pigs subjected to a single intravenous injection of the anticancer drug cisplatin (8 mg/kg b.w.), which has ototoxic side-effects. Hearing status was evaluated with acoustically-evoked frequency-specific auditory brainstem response (ABR) and hair cell counting. Finally, in vivo magnetic resonance imaging (MRI) was used to study the distribution and elimination of the chitosan-based system from the middle ear cavity; this was analyzed and compared to a hyaluronan-based system. Results Both chitosan-based IT delivery systems caused ABR threshold elevations (p<0.05) that remained after 10 days (p<0.05) without evidence of hair cell loss, although the elevations induced by Thio-25 were significantly lower than Thio-40 (p<0.05). Thio-25 significantly reduced cisplatin-induced ABR threshold elevations (p<0.05) and the loss of outer hair cells (p<0.05). IT injection of the chitosan- and hyaluronan-based systems filled up most of the middle ear space. There were no significant differences in terms of the distribution and elimination of the two systems. Conclusion Particulate chitosan is a promising drug carrier for IT administration. Future studies should attempt to demonstrate whether the physical properties of this technique allow for a reduced injection volume and thereby a less pronounced loss of conductive hearing.